Circuit board and high-speed transmission cable
The laminated circuit substrate with polyarylene sulfide resin and thermoplastic resin improves adhesion and reduces transmission loss by using a styrene-based elastomer adhesive layer, addressing bonding issues and high-frequency signal integrity.
Patent Information
- Application Number
- CN202410679149.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-29
- Filing Date
- 2024-05-29
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Circuit boards using polyphenylene sulfide resin substrates face issues with insufficient bonding strength to adhesive layers, leading to swelling and peeling during reflow processes, and high transmission loss at high frequencies.
A circuit substrate structure is developed with a laminated design comprising a polyarylene sulfide resin as the main component, combined with a thermoplastic resin having a glass transition temperature or melting point of 140°C or higher, and an adhesive layer containing a styrene-based elastomer, ensuring improved adhesion and reduced transmission loss.
The solution enhances reflow resistance and reduces transmission loss at high frequencies by improving adhesion between the insulating substrate and adhesive layer, maintaining mechanical strength and low dielectric properties.
Smart Images

Figure BDA0004865107910000041 
Figure BDA0004865107910000051 
Figure BDA0004865107910000052
Abstract
Description
Technical Field
[0001] The present invention relates to a circuit substrate including a laminated body, wherein the laminated body is formed by laminating an insulating base material and an adhesive layer with low dielectric properties, wherein the insulating base material comprises a resin composition having excellent adhesiveness, low dielectric properties and containing a polyarylene sulfide resin as a main component. In particular, the present invention relates to a circuit substrate and a high-speed transmission cable. Background Art
[0002] In recent years, in electronic devices such as personal computers and mobile terminals, along with the high-speed and large-capacity of communication, the high-frequency development of electrical signals requires a corresponding printed wiring board. In particular, the higher the frequency of the electrical signal, the greater the loss (attenuation) of the signal power, and a printed wiring board that can reduce the loss (transmission loss) of the signal power is needed. The transmission loss includes the conductor loss on the copper foil side as a conductor and the dielectric loss on the substrate side. In order to reduce the conductor loss, there is a skin effect in the high-frequency region, and the signal has the characteristic of flowing on the conductor surface, so the copper foil as a conductor is preferably used to reduce the surface roughness. On the other hand, in order to reduce the dielectric loss, it is preferably a low dielectric property of a resin substrate or an adhesive. A printed wiring board composed of a material that meets these characteristics is required as a circuit substrate with less transmission loss.
[0003] Reference 1 discloses a circuit board using polyetheretherketone, liquid crystal polymer, fluororesin, cycloolefin polymer, or polyphenylene sulfide resin as a resin substrate, having a conductor circuit on the substrate surface, and using a low dielectric adhesive in an adhesive layer, and discloses a circuit board with low transmission loss. However, the resin used in the resin substrate is an engineering plastic resin, which generally lacks adhesion, but there is no description of adhesion with the adhesive layer, and there is a possibility of expansion and peeling during reflow.
[0004] [Prior art literature]
[0005] [Patent Document]
[0006] [Patent Document 1] Japanese Patent Application Publication No. 2022-39457 Summary of the invention
[0007] [Problems to be solved by the invention]
[0008] In a circuit board composed of an insulating substrate, a metal layer, and an adhesive layer having low dielectric properties, a substrate containing an engineering plastic resin such as a polyphenylene sulfide resin, which is difficult to bond to the insulating substrate, has a problem of insufficient bonding strength with the adhesive layer, resulting in swelling and peeling during reflow. The present invention provides a circuit board having excellent reflow resistance, low transmission loss, and high frequency compatibility.
[0009] [Technical means to solve the problem]
[0010] The present inventors have conducted intensive studies and have found that the above-mentioned problems can be solved by laminating at least a metal layer (I), an insulating substrate (I) having a circuit formed on one or both sides, an adhesive layer having a specific component on the circuit-formed surface, an insulating substrate (II) or a metal layer (II) in this order, thereby completing the present invention, wherein the insulating substrate (I) comprises a resin composition of a polyarylene sulfide resin (A) as a main component and a thermoplastic resin (B) other than the polyarylene sulfide resin (A) having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher.
[0011] That is, the present invention relates to the following (1) to (11).
[0012] (1) A circuit substrate comprising a structure in which at least a metal layer (I), an insulating substrate (II) having a circuit formed on one or both sides, an adhesive layer on the circuit-formed surface side, an insulating substrate (II) or a metal layer (II) are sequentially stacked, wherein:
[0013] The insulating substrate (I) comprises a resin composition of a polyarylene sulfide resin (A) as a main component and a thermoplastic resin (B) other than the polyarylene sulfide resin having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher.
[0014] The adhesive layer is a thermosetting resin layer containing a styrene-based elastomer.
[0015] (2) The circuit board according to (1), wherein the thermoplastic resin (B) other than the polyarylene sulfide-based resin is a dispersed phase having an average dispersed diameter of 5 μm or less.
[0016] (3) The circuit board according to (1) or (2), wherein the ratio of the blending amount of the thermoplastic resin (B) other than the polyarylene sulfide resin is in the range of 1% by mass to 49% by mass relative to 100% by mass of the total amount of the polyarylene sulfide resin (A) and the thermoplastic resin (B).
[0017] (4) The circuit board according to any one of (1) to (3), wherein the thermoplastic resin (B) other than the polyarylene sulfide resin is a polyphenylene ether resin, a polycarbonate resin, a polyether sulfone resin, a polyphenylene sulfone resin, a polyetherimide resin, a polysulfone resin, or a fluorine-containing resin.
[0018] (5) The circuit board according to any one of (1) to (4), wherein the dielectric constant of the insulating base material (I) is 3.3 or less.
[0019] (6) The circuit board according to any one of (1) to (5), wherein the resin composition of the insulating base material (I) further contains a modified elastomer (C) to which a reactive group is imparted.
[0020] (7) The circuit board according to (6), wherein the modified elastomer (C) comprises an olefin-based polymer having at least one functional group selected from the group consisting of an epoxy group and an acid anhydride group.
[0021] (8) The circuit board according to (6) or (7), wherein the modified elastomer (C) is contained in an amount of 1 to 15% by mass relative to 100% by mass of the total of the polyarylene sulfide resin (A), the thermoplastic resin (B) other than polyarylene sulfide, and the modified elastomer (C).
[0022] (9) The circuit board according to any one of (6) to (8), wherein the α-olefin content of the modified elastomer (C) is 50% by mass to 95% by mass based on the total mass of the modified elastomer.
[0023] (10) The circuit board according to any one of (1) to (9), further comprising 0.01% by mass to 5% by mass of a silane coupling agent (D) containing at least one functional group selected from an epoxy group, an amino group, and an isocyanate group.
[0024] (11) A high-speed transmission cable comprising the circuit substrate according to any one of (1) to (10).
[0025] [Effects of the Invention]
[0026] According to the present invention, there is provided a circuit board which is a circuit board in which at least a metal layer (I), an insulating base material (I) having a circuit formed on one or both sides, an adhesive layer on the circuit-formed surface side, an insulating base material (II) or a metal layer (II) are sequentially laminated, wherein by using a resin composition comprising a polyarylene sulfide resin (A) as a main component and a thermoplastic resin (B) other than a polyarylene sulfide resin having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher in the insulating base material (I), the adhesion to the adhesive layer containing a styrene elastomer is improved, the reflow resistance is excellent, and the transmission loss at high frequencies can be reduced. DETAILED DESCRIPTION
[0027] Hereinafter, the mode for carrying out the present invention will be described in detail.
[0028] [Insulating substrate (I)]
[0029] The resin composition constituting the insulating substrate (I) contains a polyarylene sulfide resin (hereinafter, sometimes referred to as "PAS resin") as a main component and a thermoplastic resin other than the polyarylene sulfide resin having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher as a raw material. In this case, the resin composition has a continuous phase and a dispersed phase, the continuous phase containing the polyarylene sulfide resin, and the dispersed phase containing the thermoplastic resin (B) other than the polyarylene sulfide resin having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher. In addition, the main component in the present invention means that the polyarylene sulfide resin accounts for 51% by mass or more when the entire resin composition is 100% by mass.
[0030] The insulating substrate (I) of the present invention preferably has a dielectric constant of 3.3 or less and a dielectric loss tangent of 0.005 or less at a frequency of 5 GHz. Furthermore, it is more preferably a dielectric constant of 3.0 or less and a dielectric loss tangent of 0.004 or less. If the dielectric constant is 3.3 or less and the dielectric loss tangent is 0.005 or less, it can be suitable for use in high-frequency flexible printed circuit (Flexible Printed Circuit, FPC) related products.
[0031] The average dispersion diameter of the dispersed phase is 5 μm or less, preferably 0.5 μm or more and 5 μm or less, and more preferably 0.5 μm or more and 3 μm or less. If the average dispersion diameter of the dispersed phase is within the range of 0.5 μm or more and 5 μm or less, the physical properties as an insulating substrate can be maintained, and an insulating substrate with excellent adhesion to metal and adhesive layer can be obtained. In addition, in this specification, the "average dispersion diameter of the dispersed phase" adopts the value measured by the method described in the examples.
[0032] [Polyarylene sulfide resin (A)]
[0033] The polyarylene sulfide-based resin (A) (PAS-based resin (A)) is a main component of the resin composition and is contained in the continuous phase of the resin composition in principle.
[0034] The PAS-based resin (A) is a polymer containing a structure in which an aromatic ring and a sulfur atom are bonded to each other (specifically, a structure represented by the following formula (1)) as a repeating unit.
[0035] [Chemistry 1]
[0036]
[0037] In the formula, R 1 Each independently represents a hydrogen atom, an alkyl group having 1 to 4 carbon atoms, a nitro group, an amino group, a phenyl group, a methoxy group, or an ethoxy group, and n each independently represents an integer of 1 to 4.
[0038] Here, R in the structure represented by formula (1) 1 Preferably, all of them are hydrogen atoms. With such a structure, the mechanical strength of the PAS-based resin (A) can be further improved. 1 Examples of the structure represented by formula (1) in which all the atoms are hydrogen atoms include the structure represented by formula (2) below (i.e., a structure in which the sulfur atom is bonded to the aromatic ring at the para position) and the structure represented by formula (3) below (i.e., a structure in which the sulfur atom is bonded to the aromatic ring at the meta position).
[0039] [Chemistry 2]
[0040]
[0041] Among these, the structure represented by formula (1) is preferably the structure represented by formula (2). When the PAS-based resin (A) has the structure represented by formula (2), heat resistance and crystallinity can be further improved.
[0042] The PAS-based resin (A) may contain not only the structure represented by the above formula (1) but also the structures represented by the following formulas (4) to (7) as repeating units.
[0043] [Chemistry 3]
[0044]
[0045] The structures represented by formulae (4) to (7) preferably account for 30 mol% or less, and more preferably 10 mol% or less, of all repeating units constituting the PAS resin (A). The above structures can further improve the heat resistance or mechanical strength of the PAS resin (A).
[0046] The bonding form of the structures represented by formula (4) to formula (7) may be either random or block.
[0047] The PAS-based resin (A) may also contain a trifunctional structure represented by the following formula (8), a naphthyl sulfide structure, or the like as a repeating unit in its molecular structure.
[0048] [Chemistry 4]
[0049]
[0050] The structure represented by formula (8), naphthyl sulfide structure, etc. are preferably contained in an amount of 1 mol% or less, more preferably substantially not contained, in all repeating units constituting the PAS resin (A). Such a structure can reduce the chlorine atom content in the PAS resin (A).
[0051] In addition, the properties of the PAS-based resin (A) are not particularly limited as long as the effects of the present invention are not impaired. The melt viscosity (V6) thereof at 300°C is preferably 100 Pa·s to 2000 Pa·s, and is more preferably 120 Pa·s to 1600 Pa·s in terms of achieving a better balance between fluidity and mechanical strength.
[0052] Furthermore, the PAS resin (A) preferably has a peak in the molecular weight range of 25,000 to 40,000 in the measurement using gel permeation chromatography (GPC), and the ratio (Mw / Mn) of the weight average molecular weight (Mw) to the number average molecular weight (Mn) is in the range of 5 to 10 and the non-Newtonian index is in the range of 0.9 to 1.3. By using the PAS resin (A), the content of chlorine atoms in the PAS resin (A) itself can be reduced to within the range of 500 ppm to 2,000 ppm without reducing the mechanical strength of the insulating film 4, and it is easy to be applied to halogen-free electronic / electrical parts.
[0053] In this specification, the weight average molecular weight (Mw), the number average molecular weight (Mn), and the molecular weight distribution (Mw / Mn) are respectively the values measured by gel permeation chromatography (GPC). The measurement conditions of GPC are as follows.
[0054] [Measurement conditions by gel permeation chromatography]
[0055] Device: Ultra-high temperature polymer molecular weight distribution measuring device (SSC-7000 manufactured by Senshu Scientific)
[0056] Tube: UT-805L (manufactured by Showa Denko Co., Ltd.)
[0057] Column temperature: 210℃
[0058] Solvent: 1-Chloronaphthalene
[0059] Measurement method: The molecular weight distribution and peak molecular weight were measured using a UV detector (360 nm) and six types of monodisperse polystyrenes for calibration.
[0060] The method for producing the PAS-based resin (A) is not particularly limited, and examples thereof include: 1) a method in which a polyhalogenated aromatic compound or other copolymerization component is added to a dihalogenated aromatic compound in the presence of sulfur and sodium carbonate to polymerize the compound; 2) a method in which a polyhalogenated aromatic compound or other copolymerization component is added to a dihalogenated aromatic compound in the presence of a thioetherifying agent or the like in a polar solvent to polymerize the compound; 3) a method in which other copolymerization components are added to p-chlorothiophenol to self-condense the compound, etc. Among these production methods, the method 2) is generally used and is preferred.
[0061] Furthermore, during the reaction, an alkali metal salt of a carboxylic acid or a sulfonic acid or an alkali hydroxide may be added in order to adjust the degree of polymerization.
[0062] Among the above-mentioned method 2), the following method 2-1) or method 2-2) is particularly preferred.
[0063] In the method 2-1), an aqueous thioetherification agent is introduced into a mixture containing a heated organic polar solvent and a dihalogenated aromatic compound at a rate that can remove water from the reaction mixture. When a polyhalogenated aromatic compound is added to the dihalogenated aromatic compound and the thioetherification agent in the organic polar solvent and reacted, the amount of water in the reaction system is controlled within the range of 0.02 mol to 0.5 mol relative to 1 mol of the organic polar solvent, thereby producing a PAS-based resin (A) (see Japanese Patent Laid-Open No. 07-228699).
[0064] 2-2), in the presence of a solid alkali metal sulfide and a non-protonic polar organic solvent, a polyhalogenated aromatic compound or other copolymer components are added to a dihalogenated aromatic compound as needed, and reacted with an alkali metal hydrosulfide and an organic acid alkali metal salt, the amount of the organic acid alkali metal salt is controlled within the range of 0.01 mol to 0.9 mol relative to 1 mol of the sulfur source, and the amount of water in the reaction system is controlled within the range of 0.02 mol or less relative to 1 mol of the non-protonic polar organic solvent, thereby producing a PAS-based resin (A) (see WO2010 / 058713 manual).
[0065] Specific examples of the dihalogenated aromatic compound include p-dihalobenzene, m-dihalobenzene, o-dihalobenzene, 2,5-dihalotoluene, 1,4-dihalonaphthalene, 1-methoxy-2,5-dihalobenzene, 4,4'-dihalobiphenyl, 3,5-dihalobenzoic acid, 2,4-dihalobenzoic acid, 2,5-dihalonitrobenzene, 2,4-dihalonitrobenzene, 2,4-dihaloanisole, p,p'-dihalodiphenyl ether, 4,4'-dihalobenzophenone, 4,4'-dihalodiphenyl sulfone, 4,4'-dihalodiphenyl sulfoxide, 4,4'-dihalodiphenyl sulfide, and compounds wherein the aromatic ring of each of the above compounds has an alkyl group having 1 to 18 carbon atoms.
[0066] Examples of the polyhalogenated aromatic compound include 1,2,3-trihalobenzene, 1,2,4-trihalobenzene, 1,3,5-trihalobenzene, 1,2,3,5-tetrahalobenzene, 1,2,4,5-tetrahalobenzene, and 1,4,6-trihalonaphthalene.
[0067] Furthermore, the halogen atom contained in the above compound is preferably a chlorine atom or a bromine atom.
[0068] The reaction mixture containing the PAS-based resin (A) obtained in the polymerization step can be post-treated by a known conventional method. The post-treatment method is not particularly limited, and examples thereof include the following methods (1) to (5).
[0069] In the method (1), after the polymerization reaction is completed, the reaction mixture is first distilled under reduced pressure or normal pressure to remove the solvent directly or after adding an acid or a base. The solid matter after the solvent is distilled off is then washed once or twice with a solvent such as water, a reaction solvent (or an organic solvent having an equivalent degree of solubility for the low molecular weight polymer), acetone, methyl ethyl ketone, alcohol, etc., and then neutralized, washed with water, filtered and dried.
[0070] In the method (2), after the polymerization reaction is completed, a solvent such as water, acetone, methyl ethyl ketone, alcohols, ethers, halogenated hydrocarbons, aromatic hydrocarbons, aliphatic hydrocarbons, etc. (a solvent that is soluble in the polymerization solvent used and is at least a poor solvent relative to the PAS-based resin (A)) is added to the reaction mixture as a precipitant to precipitate solid products such as the PAS-based resin (A) and inorganic salts, which are then separated by filtration, washed, and dried.
[0071] In the method (3), after the polymerization reaction is completed, a reaction solvent (or an organic solvent having an equivalent solubility for the low molecular weight polymer) is added to the reaction mixture and stirred, and then filtered to remove the low molecular weight polymer. The mixture is then washed once or twice with a solvent such as water, acetone, methyl ethyl ketone, alcohol, etc., and then neutralized, washed with water, filtered and dried.
[0072] In the method (4), after the polymerization reaction is completed, water is added to the reaction mixture, the mixture is washed with water, filtered, and an acid is added during the washing with water, if necessary, for acid treatment, followed by drying.
[0073] In the method (5), after the polymerization reaction is completed, the reaction mixture is filtered, washed once or twice with a reaction solvent as necessary, and then washed with water, filtered, and dried.
[0074] Examples of the acid that can be used in the method (4) include saturated fatty acids such as formic acid, acetic acid, propionic acid, butyric acid, valeric acid, caproic acid, and monochloroacetic acid, unsaturated fatty acids such as acrylic acid, crotonic acid, and oleic acid, aromatic carboxylic acids such as benzoic acid, phthalic acid, and salicylic acid, dicarboxylic acids such as maleic acid and fumaric acid, organic acids such as sulfonic acids such as methanesulfonic acid and p-toluenesulfonic acid, and inorganic acids such as hydrochloric acid, sulfuric acid, sulfurous acid, nitric acid, nitrous acid, and phosphoric acid.
[0075] Examples of the hydrogen salt include sodium hydrogen sulfide, disodium hydrogen phosphate, sodium hydrogen carbonate, etc. However, when used in an actual device, an organic acid that has little corrosion to metal parts is preferred.
[0076] In the methods (1) to (5) above, the drying of the PAS-based resin (A) may be performed in a vacuum, or in an atmosphere of an inert gas such as air or nitrogen.
[0077] In particular, the PAS-based resin (A) post-treated by the method (4) increases the amount of acid groups bonded to the molecular ends, and when mixed with the modified elastomer (C), the dispersibility of these groups can be improved. The acid groups are particularly preferably carboxyl groups.
[0078] The content of the PAS resin (A) in the resin composition may be 50% to 93% by mass, preferably 55% to 90% by mass. When the content of the PAS resin (A) is within the above range, the heat resistance and chemical resistance of the resin layer can be further improved.
[0079] [Thermoplastic resin (B) other than polyarylene sulfide resin]
[0080] The thermoplastic resin (B) other than the polyarylene sulfide resin (A) of the present invention (hereinafter sometimes referred to as "thermoplastic resin (B)") can be any thermoplastic resin other than the PAS resin having a glass transition temperature of 140°C or higher or a melting point of 230°C or higher. If the thermoplastic resin (B) has a glass transition temperature of 140°C or higher or a melting point of 230°C or higher, a significant decrease in heat resistance can be suppressed, and the surface modification effect by corona treatment or plasma treatment can be improved, thereby improving adhesion. In addition, the affinity with the styrene elastomer contained in the adhesive layer can be improved, and the laminate including the insulating substrate (I) containing the resin composition of the present invention and the adhesive layer has high adhesion.
[0081] As the thermoplastic resin (B) other than the PAS-based resin (A), any thermoplastic resin having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher may be used, for example, various polymers such as polycarbonate, polyphenylene ether, polyether sulfone, polyphenylene sulfone, polyetherimide, polysulfone, fluorine-containing resin, and dopants containing at least one of these polymers may be used. Among them, polyphenylene ether or fluorine-containing resin is preferred from the viewpoint of low dielectric properties, miscibility with PAS, affinity with an adhesive layer containing a styrene-based elastomer, and low hygroscopicity.
[0082] The content of the thermoplastic resin (B) in the resin composition constituting the resin layer may be 1% to 49% by mass, but is preferably 3% to 40% by mass. If the content of the thermoplastic resin (B) is within the above range, the physical properties of the insulating substrate are maintained and the adhesion to the adhesive layer is effective.
[0083] Polyphenylene ether resin (hereinafter sometimes referred to as "PPE resin") is a component having the function of lowering the dielectric constant and dielectric loss tangent of the insulating substrate (I). It is highly compatible with the styrene part of the styrene elastomer contained in the adhesive layer, and thus can improve the adhesion, so it is preferred.
[0084] The PPE-based resin is a polymer containing a structure represented by the following formula (9) as a repeating unit.
[0085] [Chemistry 5]
[0086]
[0087] In the formula, R 2 Each of them is independently a hydrogen atom, a halogen atom, a primary alkyl group having 1 to 7 carbon atoms, a secondary alkyl group having 1 to 7 carbon atoms, a phenyl group, a halogenated alkyl group, an aminoalkyl group, an alkyloxy group, or a halogenated alkyloxy group in which at least two carbon atoms separate the halogen atom from the oxygen atom, and m is independently an integer of 1 to 4.
[0088] Specific examples of PPE-based resins include homopolymers such as poly(2,6-dimethyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), and poly(2,6-dichloro-1,4-phenylene ether); and copolymers of 2,6-dimethylphenol and other phenols (e.g., 2,3,6-trimethylphenol or 2-methyl-6-butylphenol).
[0089] Among these, the PPE-based resin is preferably poly(2,6-dimethyl-1,4-phenylene ether) or a copolymer of 2,6-dimethylphenol and 2,3,6-trimethylphenol, and more preferably poly(2,6-dimethyl-1,4-phenylene ether).
[0090] The number average molecular weight of the PPE-based resin is preferably 1,000 or more, more preferably 1,500 to 50,000, and still more preferably 1,500 to 30,000.
[0091] In terms of low dielectric properties, fluorine-containing resins are preferably used as thermoplastic resins (B), preferably having at least one reactive functional group selected from the group consisting of a carbonyl-containing group, a hydroxyl group, an epoxy group, and an isocyanate group. These reactive functional groups may also contain two or more. Among them, in terms of excellent reactivity with PAS-based resins (A), carbonyl-containing groups are preferred. As carbonyl-containing groups, groups having carbonyl groups between carbon atoms of hydrocarbon groups, carbonate groups, carboxyl groups, haloformyl groups, alkoxycarbonyl groups, acid anhydride groups, polyfluoroalkoxycarbonyl groups, etc. can be cited.
[0092] As a method for introducing reactive functional groups into a fluorine-containing resin, (1) when manufacturing the main chain of a fluorine-containing resin having a reactive functional group by a polymerization reaction, a monomer having a reactive functional group is used. (2) A chain transfer agent that generates free radicals having a reactive functional group is used to manufacture a fluorine-containing resin having a functional group by a polymerization reaction. (3) A polymerization initiator that generates free radicals having a reactive functional group is used to manufacture a fluorine-containing resin having a functional group by a polymerization reaction. Examples include (4) a method of modifying a fluorine-containing resin by oxidation, thermal decomposition, etc. In addition, examples include (5) a method of preparing a compound or resin that is compatible with the fluorine-containing resin and contains the functional group.
[0093] Examples of the reactive functional group-containing monomer include a monomer having a carbonyl group-containing group, an epoxy group-containing monomer, a hydroxyl group-containing monomer, and an isocyanate group-containing monomer.
[0094] Examples of the monomer having a carbonyl-containing group include unsaturated dicarboxylic acids (maleic acid, itaconic acid, citraconic acid, crotonic acid, bicycloheptenedicarboxylic acid, 5-norbornene-2,3-dicarboxylic acid, maleic acid), unsaturated dicarboxylic anhydrides thereof, unsaturated monocarboxylic acids (acrylic acid, methacrylic acid), vinyl esters (vinyl acetate, vinyl chloroacetate, vinyl butyrate, vinyl trimethylacetate, vinyl benzoate, vinyl crotonate), and the like.
[0095] Examples of the hydroxyl group-containing monomer include hydroxyl group-containing vinyl esters, hydroxyl group-containing vinyl ethers, hydroxyl group-containing allyl ethers, hydroxyl group-containing (meth)acrylates, hydroxyethyl crotonate, and allyl alcohol.
[0096] Examples of the epoxy group-containing monomer include unsaturated glycidyl ethers (allyl glycidyl ether, 2-methylallyl glycidyl ether, vinyl glycidyl ether, etc.) and unsaturated glycidyl esters (glycidyl acrylate, glycidyl methacrylate, etc.).
[0097] As the isocyanate group-containing monomer, 2-(meth)acryloyloxyethyl isocyanate, 2-(2-(meth)acryloyloxyethoxy)ethyl isocyanate, 1,1-bis((meth)acryloyloxymethyl)ethyl isocyanate, etc. can be mentioned.
[0098] The amount of reactive functional groups contained in the fluorine-containing resin is preferably 0.01 mol% to 3 mol%, more preferably 0.03 mol% to 2 mol%, and further preferably 0.05 mol% to 1 mol% in all units constituting the fluorine-containing resin. If the amount of reactive functional groups is within the above range, the reactivity with the PAS-based resin is excellent and deterioration of fluidity can be suppressed.
[0099] The structure of fluorine-containing resin is not particularly limited, and is composed of at least one fluoroolefin unit. For example, tetrafluoroethylene polymers or copolymers with perfluoro (alkyl vinyl ether), hexafluoropropylene, vinylidene fluoride, fluorinated vinyl, trifluoroethylene, chlorotrifluoroethylene, and copolymers with fluorine-free non-fluorinated vinyl monomers such as ethylene, propylene, butene, and alkyl vinyl ethers can also be cited. Specifically, polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymers, tetrafluoroethylene-perfluoro (alkyl vinyl ether) copolymers, tetrafluoroethylene-hexafluoropropylene copolymers, ethylene-tetrafluoroethylene-hexafluoropropylene copolymers, polyvinylidene fluoride, polychlorotrifluoroethylene, etc. can be cited. Among them, in terms of easy melt extrusion, preferably ethylene-tetrafluoroethylene copolymers, tetrafluoroethylene-perfluoro (alkyl vinyl ether) copolymers, tetrafluoroethylene-hexafluoropropylene copolymers.
[0100] The melting point of the fluorine-containing resin used in the present invention is not particularly limited, but is preferably 230° C. or higher, more preferably 270° C. or higher. When the melting point of the fluorine-containing resin is within the above range, heat resistance can be maintained and good melt extrusion stability can be obtained.
[0101] The glass transition temperature of the fluorine-containing resin used in the present invention is not particularly limited, and is 130° C. or less, more preferably 120° C. or less, or 110° C. or less. If the fluorine-containing resin has the above glass transition temperature, when a mixture with the PAS-based resin (A) is used to make a stretched film (a form of an insulating substrate), the peeling at the interface between the PAS-based resin (A) as a continuous phase and the fluorine-containing resin as a dispersed phase can be suppressed during stretching. Thus, the breakage during stretching can be suppressed, and a film with excellent mechanical properties can be obtained.
[0102] [Modified elastomer (C)]
[0103] The modified elastomer (C) is contained in the dispersed phase of the resin composition constituting the insulating substrate (I) in principle. The modified elastomer (C) has the following functions: the mechanical strength (tensile properties, folding strength, etc.) of the laminate is improved by having a reactive group that can react with at least one of the PAS-based resin (A) and the thermoplastic resin (B). In addition, the modified elastomer (C) has excellent affinity with the styrene-based elastomer contained in the adhesive layer, thereby improving the adhesiveness.
[0104] The reactive group of the modified elastomer (C) is preferably at least one selected from the group consisting of epoxy groups and acid anhydride groups, and more preferably epoxy groups. These reactive groups can react rapidly with the functional groups at the molecular terminals of the PAS-based resin (A) and the thermoplastic resin (B).
[0105] Examples of the modified elastomer (C) include copolymers comprising repeating units based on α-olefins and repeating units based on a vinyl polymerizable compound having the functional group, copolymers comprising repeating units based on α-olefins, repeating units based on a vinyl polymerizable compound having the functional group and repeating units based on acrylates, and the like.
[0106] Examples of the α-olefin include α-olefins having 2 to 8 carbon atoms, such as ethylene, propylene, and butene-1.
[0107] Examples of the vinyl polymerizable compound having a functional group include α,β-unsaturated carboxylic acids and esters thereof such as acrylic acid, methacrylic acid, acrylic acid esters, and methacrylic acid esters; maleic acid, fumaric acid, itaconic acid; other unsaturated dicarboxylic acids having 4 to 10 carbon atoms; their monoesters and diesters; their anhydrides; α,β-unsaturated dicarboxylic acids; their esters; their anhydrides; and α,β-unsaturated glycidyl esters.
[0108] The α,β-unsaturated glycidyl ester is not particularly limited, and examples thereof include compounds represented by the following formula (10).
[0109] [Chemistry 6]
[0110]
[0111] In the formula, R 3 It is an alkenyl group having 1 to 6 carbon atoms.
[0112] Examples of the alkenyl group having 1 to 6 carbon atoms include ethenyl, 1-propenyl, 2-propenyl, 1-methylethenyl, 1-butenyl, 2-butenyl, 1-methyl-1-propenyl, 1-methyl-2-propenyl, 2-methyl-1-propenyl, 2-methyl-2-propenyl, 1-pentenyl, 2-pentenyl, 3-pentenyl, 4-pentenyl, 1-methyl-1-pentenyl, 1-methyl-3-pentenyl, 1,1-dimethyl-1-butenyl, 1-hexenyl, and 3-hexenyl.
[0113] R 4 Each independently represents a hydrogen atom, a halogen atom, or an alkyl group having 1 to 6 carbon atoms.
[0114] Examples of the halogen atom include a fluorine atom, a chlorine atom, a bromine atom and an iodine atom.
[0115] Examples of the alkyl group having 1 to 6 carbon atoms include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, sec-butyl, tert-butyl, pentyl, 2-methylbutyl, 3-methylbutyl, 2,2-dimethylpropyl, hexyl, 1-methylpentyl, 2-methylpentyl, 3-methylpentyl, 4-methylpentyl, 2,2-dimethylbutyl, 2,3-dimethylbutyl, 2,4-dimethylbutyl, 3,3-dimethylbutyl, and 2-ethylbutyl.
[0116] Specific examples of the α,β-unsaturated glycidyl ester include glycidyl acrylate and glycidyl methacrylate, and glycidyl methacrylate is preferred.
[0117] The proportion of the repeating unit based on α-olefin in the modified elastomer (C) is preferably 50% to 95% by mass, more preferably 50% to 80% by mass. If the proportion of the repeating unit based on α-olefin is within the above range, the stretching uniformity, folding strength and bonding strength of the film as an insulating substrate can be improved.
[0118] In addition, the ratio of the repeating unit based on the vinyl polymerizable compound having a functional group in the modified elastomer (C) is preferably 1% to 30% by mass, and more preferably 2% to 20% by mass. If the ratio of the repeating unit based on the vinyl polymerizable compound having a functional group is within the above range, not only the target improvement effect can be obtained, but also good extrusion stability can be obtained.
[0119] The content of the modified elastomer (C) in the resin composition constituting the insulating substrate (I) is preferably 1% to 15% by mass, more preferably 2% to 10% by mass. If the content of the modified elastomer (C) is within the above range, the effect of improving the folding strength and adhesive strength of the laminate can be significantly exerted.
[0120] [Silane coupling agent (D)]
[0121] In the present invention, a silane coupling agent is preferably used as a component having a function of improving the compatibility and interaction between the PAS-based resin (A) and other components (thermoplastic resin (B) other than the PAS-based resin, modified elastomer (C)), so that the dispersibility of other components in the PAS-based resin (A) is greatly improved, and a good morphology can be formed.
[0122] The silane coupling agent (D) is preferably a compound having a functional group that can react with a carboxyl group. The silane coupling agent reacts with other components to firmly bond with them. As a result, the effect of the silane coupling agent can be more significantly exerted, and the dispersibility of other components in the PAS-based resin (A) can be particularly improved.
[0123] Examples of the silane coupling agent include compounds having an epoxy group, an isocyanate group, an amino group, or a hydroxyl group.
[0124] Specific examples of the silane coupling agent include epoxy group-containing alkoxysilane compounds such as γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, γ-isocyanatopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, γ-isocyanatopropylmethyldimethoxysilane, γ-isocyanatopropylmethyldiethoxysilane, γ-isocyanatopropylethyl Alkoxysilane compounds containing isocyanate groups such as dimethoxysilane, γ-isocyanatepropylethyldiethoxysilane, and γ-isocyanatepropyltrichlorosilane, alkoxysilane compounds containing amino groups such as γ-(2-aminoethyl)aminopropylmethyldimethoxysilane, γ-(2-aminoethyl)aminopropyltrimethoxysilane, and γ-aminopropyltrimethoxysilane, and alkoxysilane compounds containing hydroxy groups such as γ-hydroxypropyltrimethoxysilane and γ-hydroxypropyltriethoxysilane.
[0125] The content of the silane coupling agent in the resin composition constituting the insulating substrate (I) is preferably 0.01% to 5% by mass, more preferably 0.05% to 2.5% by mass. When the content of the silane coupling agent is within the above range, the dispersibility of other components in the PAS-based resin (A) can be significantly improved.
[0126] [Metal layer (I), Metal layer (II)]
[0127] As the metal layer (conductor layer), it is preferred to use a foil of copper, aluminum, iron, gold, silver, nickel, palladium, chromium, molybdenum or an alloy thereof. Among them, from the viewpoints of processability, bendability, electrical conductivity, etc., copper foil is preferred. Examples of copper foil include rolled copper foil, electrolytic copper foil, etc. The thickness of the copper foil is preferably between 1 μm and 50 μm, and more preferably between 1 μm and 30 μm. In addition, the copper foil may also be subjected to various surface treatments (roughening, rust-proofing, etc.). As rust-proofing treatment, examples include mirror finishing treatments such as plating treatments including Ni, Zn, Sn, etc., and chromate treatments. In addition, the metal layer (I) and the metal layer (II) may be the same metal layer or different metal layers.
[0128] In order to make the circuit board using the copper-clad laminate obtained by the present invention show good high-frequency characteristics, the surface roughness of the metal layer (I) on the side in contact with the insulating substrate (I) is as low as possible. The surface roughness Rz of the metal layer (I) on the side in contact with the insulating substrate (I) is preferably 2 μm or less, and further, more preferably 1.5 μm or less, and further preferably no roughening.
[0129] [Adhesive layer]
[0130] The bonding layer is used for the interlayer bonding of the multilayer flexible wiring board or the reinforcing plate bonding of the flexible wiring board, and is called a bonding sheet. It is not particularly limited, but from the perspective of good bonding to the circuit forming layer formed by the metal layer (I) and the insulating substrate (I) of the resin composition containing the polyarylene sulfide resin as the main component, the embedding property of the circuit pattern is excellent, and the low dielectric properties are preferably included. A thermosetting resin containing a styrene elastomer is used as the main component. In addition, in addition to the thermosetting resin, a curing agent or a curing accelerator, a flexible component, an inorganic filler, and an additive of a flame retardant may also be included as needed.
[0131] Styrene elastomer is a copolymer of styrene and olefin (e.g., conjugated dienes such as butadiene and isoprene) and / or its hydrogenate. Styrene elastomer is a block copolymer using styrene as a hard segment and a conjugated diene as a soft segment. Examples of styrene elastomers include: styrene / butadiene / styrene block copolymer, styrene / isoprene / styrene block copolymer, styrene / ethylene / butylene / styrene block copolymer, styrene / ethylene / propylene / styrene block copolymer, styrene / butadiene block copolymer, etc. In addition, styrene / ethylene / butylene / styrene block copolymer, styrene / ethylene / propylene / styrene block copolymer, styrene / butadiene block copolymer (also referred to as hydrogenated styrene elastomer), etc., which eliminate the double bonds of the conjugated diene component by hydrogenation, can also be used. Styrene elastomer can be used one or two or more.
[0132] Styrene elastomers may also have functional groups such as carboxyl or glycidyl. The modification of styrene elastomers containing functional groups can be carried out, for example, by copolymerizing unsaturated carboxylic acids during polymerization of styrene elastomers. In addition, the modification can also be carried out by heating and kneading styrene elastomers and unsaturated carboxylic acids in the presence of organic peroxides. Examples of unsaturated carboxylic acids include acrylic acid, methacrylic acid, maleic acid, itaconic acid, fumaric acid, maleic anhydride, itaconic anhydride, and fumaric anhydride. The amount of modification caused by the unsaturated carboxylic acid is preferably 0.1% to 10% by mass.
[0133] The weight average molecular weight of the styrene elastomer is preferably 10000 or more, more preferably 100000 to 300000, and further preferably 50000 to 250000. By adopting such a structure, the bonding strength (connection reliability), bending property, and followability can be improved.
[0134] The styrene ratio in the styrene elastomer is preferably less than 50%, more preferably 5% to 45%, and further preferably 10% to 40%. By adopting such a structure, the bending resistance can be improved, and the bonding strength (connection reliability), bending property, and tracking property can be improved.
[0135] The content of the styrene-based elastomer in the adhesive layer is preferably 50% by mass or more relative to 100% by mass of the solid content of the adhesive layer. If it is less than 50% by mass, the adhesive strength, bending resistance and followability are poor.
[0136] As a thermosetting resin containing a styrene-based elastomer, one or more known thermosetting resins can be used in combination. In particular, from the viewpoint of heat resistance, epoxy compounds can be preferably used. Epoxy compounds are compounds containing at least two or more epoxy groups in the molecule, for example, bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol S epoxy resin, bisphenol AD epoxy resin, resorcinol epoxy resin, hydroquinone epoxy resin, catechol epoxy resin, hydroxynaphthalene epoxy resin, biphenyl epoxy resin, tetramethylbiphenyl epoxy resin, phenol novolac epoxy resin, cresol novolac epoxy resin, etc. Epoxy resins can be used alone or in combination of two or more.
[0137] Examples of the curing agent after curing include amine compounds such as dicyandiamide, diaminodiphenylmethane, diaminodiphenyl sulfide, diaminobenzophenone, diaminodiphenyl sulfone, and diethyltriamine; imidazole derivatives such as 2-alkyl-4-methylimidazole, 2-phenyl-4-alkylimidazole, 2-phenyl-4-alkylimidazole, and 1-cyanoethyl-2-methylimidazole; 1,8-diazabicyclo[5,4,0]undecene, 7,1,4-diazabicyclo[2,2,2]octane and other 1,8-diazabicyclo[5.4.0]undec-7-ene (DBU) compounds; triphenylphosphine; and triethylamine. Phosphorus compounds such as methylphosphine, aromatic tertiary amines such as benzyldimethylamine, 2-(dimethylamino)phenol, and 2,4,6-tris(diaminomethyl)phenol, alicyclic tertiary amines such as dimethylcyclohexylamine, organic acids such as phthalic anhydride, trimellitic anhydride, and pyromellitic acid, amine complexes of boron trifluoride such as boron triethylamine complex and boron trifluoride piperazine complex, amine complexes of boron trichloride, phosphorus pentafluoride, arsenic pentafluoride, antimony pentafluoride, boron tetrafluoride amine complex, boron trifluoride piperazine complex and other amine complexes, amine complexes of boron trichloride, phosphorus pentafluoride, arsenic pentafluoride, antimony pentafluoride, boron tetrafluoride amine salt, metal borofluorides such as zinc borofluoride, etc., can be used alone or in combination of two or more. In addition, phenol resins such as resol type phenol resins and novolac type phenol resins can also be used. Examples of the phenol resins include alkyl-substituted phenols such as phenol, biphenol, and cresol, cyclic alkyl-modified phenols such as terpenes and dicyclopentadiene, substances having functional groups containing hetero atoms such as nitro and amino groups, and substances having skeletons such as naphthalene and anthracene.
[0138] Furthermore, the thermosetting resin may be added together with a curing accelerator, a flexible component, an inorganic filler, and a flame retardant as necessary.
[0139] As the flexible component, known substances can be used. For example, various synthetic rubbers such as acrylic rubber, acrylonitrile butadiene rubber, carboxyl-containing acrylonitrile butadiene rubber, rubber-modified high molecular weight compounds, modified polyimide, modified polyamide-imide, polyurethane resin, polyester resin, polyurethane polyester resin, polyvinyl butyral resin, polyvinyl acetal resin, phenoxy resin, etc. can be used. These components can be used alone or in combination of two or more.
[0140] As the inorganic filler, known materials can be used. Examples thereof include silicon dioxide, aluminum oxide, silicon nitride, aluminum hydroxide, magnesium hydroxide, talc, clay, etc. These fillers can be used alone or in combination of two or more.
[0141] As flame retardants, known substances can be used. For example, compounds containing phosphorus atoms, compounds containing nitrogen atoms, or inorganic flame retardant compounds can be listed. Specifically, phosphoric acid esters such as trimethyl phosphate, triethyl phosphate, tributyl phosphate, tri-2-ethylhexyl phosphate, tributoxyethyl phosphate, triphenyl phosphate, tricresyl phosphate, and tricresyl phosphate, ammonium polyphosphate, polyphosphoric acid amide, red phosphorus, guanidine phosphate, condensed phosphate compounds such as dialkyl hydroxymethyl phosphate, compounds containing phosphorus atoms, nitrogen atoms such as melamine, aluminum hydroxide, magnesium hydroxide, zinc borate, inorganic flame retardant compounds such as calcium borate, etc. can be listed. These components can be used alone or in combination of two or more.
[0142] The thickness of the adhesive layer after curing is preferably 1 μm or more and 100 μm or less, more preferably 5 μm or more and 70 μm or less, and still more preferably 10 μm or more and 50 μm or less.
[0143] After the adhesive layer is cured, the dielectric constant at a frequency of 5 GHz is preferably 3.5 or less and the dielectric loss tangent is 0.01 or less. Furthermore, the dielectric constant is more preferably 3.5 or less and the dielectric loss tangent is 0.007 or less. If the dielectric constant is 3.5 or less and the dielectric loss tangent is 0.01 or less, it can also be suitable for FPC-related products with strict electrical properties.
[0144] [Insulating substrate (II)]
[0145] The resin composition constituting the insulating substrate (II) may be any substrate containing various polymers such as polyimide, liquid crystal polymer, polycarbonate, polyphenylene ether, polyether sulfone, polyphenyl sulfone, polyetherimide, polysulfone, fluorine-containing resin, and dopants containing at least one of these polymers, and may also be the insulating substrate (I).
[0146] [Additives for Insulating Base Material (I)]
[0147] The composition of the insulating substrate (I) may contain a plasticizer, a weathering agent, an antioxidant, a heat stabilizer, a UV stabilizer, a lubricant, an antistatic agent, a colorant, a conductive agent, a flame retardant, etc., as long as the effect of the present invention is not impaired.
[0148] The method for producing the resin composition of the insulating substrate (I) is not particularly limited, and examples thereof include a method in which the PAS-based resin (A) and other components (thermoplastic resin (B) other than the PAS-based resin) and other components as required (modified elastomer (C), silane coupling agent (D), etc.) are uniformly mixed using a tumbler or Henschel mixer, and then the mixture is fed into a twin-screw extruder for melt kneading. The melt kneading may be either or both of kneading in a shear flow field and kneading in an extension flow field.
[0149] The melt kneading is preferably performed under the condition that the ratio of the discharge amount (kg / hr) of the kneaded material to the screw speed (rpm) (discharge amount / screw speed) is 0.02 (kg / hr·rpm) to 0.2 (kg / hr·rpm).
[0150] If described in more detail, the following method is preferred: each component is put into a twin-screw extruder, and melt-kneading is performed under the temperature conditions of a set temperature of 300°C and a resin temperature of about 330°C in a strand die. At this time, the ejection amount of the kneaded product is in the range of 5kg / hr to 50kg / hr at a rotation speed of 250rpm. In particular, from the perspective of improving the dispersibility of each component, the ejection amount of the kneaded product is preferably 20kg / hr to 35kg / hr at a rotation speed of 250rpm. Therefore, the ratio of the ejection amount (kg / hr) of the kneaded product to the screw speed (rpm) (ejection amount / screw speed) is more preferably 0.08 (kg / hr·rpm) to 0.14 (kg / hr·rpm).
[0151] [Insulating substrate (I) (film) containing PAS-based resin (A) as main component]
[0152] One of the methods for forming the insulating substrate (I) of the present invention is to use a film obtained from a resin composition containing a PAS-based resin (A) as a main component, and a biaxially stretched film is preferred. By using a biaxially stretched film, heat resistance can be improved.
[0153] In one embodiment of the film, the PAS-based resin (A) serves as a matrix (continuous phase), and particles (dispersed phase) containing a thermoplastic resin (B) other than the PAS-based resin are dispersed in the matrix.
[0154] Furthermore, the modified elastomer (C) exists on the surface of the particles of the thermoplastic resin (B) (i.e., the interface between the matrix and the particles), exists within the particles of the thermoplastic resin (B), or exists in the form of particles (dispersed phase) different from the particles of the thermoplastic resin (B).
[0155] In addition, the present inventors and others believe that the modified elastomer (C) also functions as a compatibilizer for PAS-based resin (A) and thermoplastic resin (B), and thus the particles are micro-dispersed in the matrix, thereby suppressing the rupture of the film during stretching, improving the mechanical strength (folding strength, etc.) of the biaxially stretched film, and improving the mechanical strength in the laminate. In addition, due to the excellent affinity with the styrene-based elastomer contained in the adhesive layer, the adhesion is improved. Furthermore, it is also believed that by using the modified elastomer (C) in combination with a silane coupling agent, the adhesion at the interface between the matrix and the particles is further improved, and the mechanical strength (folding strength, etc.) of the biaxially stretched film and the laminate is further improved.
[0156] The average particle size (average dispersion diameter) of the particles (dispersed phase) dispersed in the matrix in the film state is preferably 5 μm or less, more preferably 0.5 μm or more and 5 μm or less, and further preferably 0.5 μm or more and 3 μm or less. If the average particle size of the particles is within the above range, the performance as a biaxially stretched film and a substrate is maintained, and the adhesion with the metal layer (I), the metal layer (II) or the adhesive layer is good.
[0157] The film is preferably a biaxially stretched film obtained by biaxially stretching an unstretched sheet obtained from a resin composition constituting the insulating base material (I).
[0158] The biaxially stretched film may have at least one layer containing the resin composition constituting the insulating substrate (I) of the present invention as the outermost layer, and may be a multilayer film in which layers containing other resin compositions are laminated directly or via an adhesive layer or the like.
[0159] The method for producing the biaxially stretched laminated film used in the present invention is not particularly limited. For example, in the case of forming a laminated structure, the following coextrusion method can be cited, wherein the resin or resin mixture used in each resin layer is heated and melted by respective extruders, and laminated in a molten state with a target laminated structure by a coextrusion lamination die method or a feedblock method, and then formed into a sheet by an inflation or T-die / cooling roll method, etc. The coextrusion method can adjust the ratio of the thickness of each layer more freely, and can obtain an unstretched laminated sheet with excellent cost performance, so it is preferred.
[0160] Next, in the case of biaxial stretching, the obtained unstretched sheet and unstretched laminated sheet are biaxially stretched.
[0161] As the stretching method, a sequential biaxial stretching method, a simultaneous biaxial stretching method, or a method combining these methods can be used.
[0162] When biaxial stretching is performed by a sequential biaxial stretching method, the unstretched sheet is heated, for example, by a heating roller group, stretched in the length direction (machine direction, MD direction) by 1.5 to 4 times (preferably 2 to 3.8 times) and in one or more stages, and then cooled by a cooling roller group at 30°C to 60°C.
[0163] The stretching temperature is preferably the glass transition temperature (Tg) of the PAS-based resin (A) to Tg+40°C, more preferably Tg+5°C to Tg+30°C, and still more preferably Tg+5°C to Tg+20°C.
[0164] Next, the film is stretched in the width direction (transverse direction (TD)) by using a tenter. Both ends of the film stretched in the MD direction are gripped with clips and guided to the tenter to be stretched in the TD direction.
[0165] Furthermore, the stretching ratio is preferably 1.5 to 4 times, and more preferably 2 to 3.8 times.
[0166] The stretching temperature is preferably Tg to Tg+40°C, more preferably Tg+5°C to Tg+30°C, and still more preferably Tg+5°C to Tg+20°C.
[0167] Next, the stretched film is heat-fixed while being stretched or relaxed in the width direction.
[0168] The heat setting temperature is not particularly limited, but is preferably 200°C to 280°C, more preferably 220°C to 280°C, and further preferably 240°C to 275°C. In addition, the heat setting may be performed in two stages by changing the heat setting temperature. In the above case, it is preferred that the heat setting temperature of the second stage is higher by +10°C to 40°C than the heat setting temperature of the first stage. The heat resistance and mechanical strength of the stretched film heat-set at the heat setting temperature within the above range are further improved.
[0169] In addition, the heat setting time is preferably 1 second to 60 seconds.
[0170] Furthermore, the film is cooled while being relaxed in the width direction in a temperature range of 50° C. to 275° C. The relaxation rate is preferably 0.5% to 10%, more preferably 2% to 9%, and even more preferably 3% to 8%.
[0171] In order to improve the thermal stability of such a film, heat treatment (annealing treatment) can also be performed. As a heat treatment method after stretching, for example, known methods such as a method of blowing hot air, a method of irradiating infrared rays, and a method of irradiating microwaves can be listed. Among them, in terms of being able to heat evenly and accurately, a method of blowing hot air is preferred. The heat treatment temperature is preferably set to 150°C to 260°C, and more preferably to 160°C to 240°C. If the heat treatment is not performed, the stress relaxation of the film is difficult. In addition, sufficient stress relaxation cannot be performed in the heat treatment at a temperature below 150°C, and the thermal shrinkage of the film after production cannot be reduced. As a result, it is not easy to achieve improved thermal stability of the film. In addition, when the heat treatment temperature is above 260°C, part of the crystalline phase of polyphenylene sulfide melts and the orientation is destroyed. Therefore, the linear expansion coefficient in the plane direction of the film after production deteriorates. As a result, it is not easy to achieve improved thermal stability of the film. The heat treatment time is preferably set to 3 seconds to 300 seconds, and more preferably to 5 seconds to 100 seconds.
[0172] The thickness of the biaxially stretched film or the biaxially stretched laminated film (hereinafter, the two biaxially stretched films are sometimes referred to as "stretched films") is not particularly limited, but is preferably 10 μm to 300 μm, more preferably 10 μm to 200 μm, and further preferably 10 μm to 150 μm. If the stretched film has such a thickness, a substrate having sufficient mechanical strength and insulation properties can be obtained.
[0173] The stretched film of the present invention may also be subjected to surface treatment for the purpose of improving the adhesion between the stretched film and the copper foil or the adhesive layer. Examples of the surface treatment include corona discharge treatment (including corona treatment under various gas environments), plasma treatment (including plasma treatment under various gas environments), oxidation treatment using chemicals or ultraviolet rays, electron irradiation rays, etc.
[0174] [Circuit formation]
[0175] The circuit forming layer of the present invention is formed by a laminate comprising an insulating substrate (I) and a metal layer (I). The circuit forming method is not particularly limited, and examples thereof include a method of forming an unpatterned metal layer (I) and then patterning it by etching or the like; a method of directly forming the metal layer (I) at a location required for the circuit pattern on the insulating substrate; a method of combining the two, and the circuit can be formed by a subtractive method, a semi-additive method, a full-additive method, or the like.
[0176] The laminate comprising an insulating substrate (I) and a metal layer (I) of the present invention is a laminate having a metal layer (I) directly or via an adhesive layer or a close-contact layer on an insulating substrate (I). For example, there are methods such as laminating an insulating substrate (I) and a copper foil by thermal lamination, applying a resin solution for forming an adhesive layer on the surface of an insulating substrate (I) and drying it, or thermally laminating a film containing an adhesive agent to an insulating substrate (I) to prepare an insulating substrate (I) having an adhesive layer in an uncured state, and then laminating the adhesive layer side to the copper foil.
[0177] Alternatively, a nickel alloy may also be used as a close-contact layer. Among them, in terms of etching or close-contact properties, a nickel-copper alloy is preferably used, which is suitable for high-frequency circuit substrates. As a method for forming a close-contact layer comprising a nickel alloy, for example, various sputtering methods, evaporation methods, ion plating methods, etc. represented by a direct current (DC) magnetron sputtering method using a nickel-copper alloy as a material, and a method of treating the entire surface of the insulating substrate (I) and the like. After forming the close-contact layer, a metal layer (I) of copper or the like of a specified thickness is formed by electrolytic plating.
[0178] The thickness of the adhesion layer is preferably 3 nm or more and 100 nm or less. Since the conductivity of nickel alloy is lower than that of copper, if the thickness of the adhesion layer is thicker than 100 nm, it may have an adverse effect on signal transmission.
[0179] In one embodiment, the stack may have the following structures: metal layer (I)-insulating substrate, metal layer (I)-adhesive layer-insulating substrate, metal layer (I)-closed layer-insulating substrate, metal layer (I)-insulating substrate-metal layer (I), metal layer (I)-adhesive layer-insulating substrate-adhesive layer-metal layer (I), metal layer (I)-closed layer-insulating substrate-closed layer-metal layer (I), metal layer (I)-closed layer-extended substrate-adhesive layer-metal layer (I)-closed layer-insulating substrate, metal layer (I)-closed layer-extended substrate-closed layer-metal layer (I)-closed layer-insulating substrate, and the like.
[0180] [Circuit Evaluation]
[0181] 1. Dielectric properties of insulating substrate (I)
[0182] The dielectric constant and dielectric loss tangent are measured based on the cavity resonance method specified in Japanese Industrial Standards (JIS) C 2565:1992. Specifically, a strip of 3 mm wide × 150 mm long is made from an insulating substrate (I). Next, the produced strip is left to stand for 24 hours under an environment of 23°C and 50% Rh, and then the dielectric constant and dielectric loss tangent at a frequency of 5 GHz are measured using the cavity resonance method using the ADMS010c series (manufactured by Aet Co., Ltd.). The dielectric properties of the insulating substrate of the high-frequency circuit substrate are preferably a dielectric constant of less than 3.3 and a dielectric loss tangent of less than 0.005 at a frequency of 5 GHz.
[0183] 2. Adhesion to the adhesive layer
[0184] The bonding layer (thickness 25μm, 100mm×100mm) is overlapped with the insulating substrate (I) (100mm×100mm), and after being pressed at 80°C and 0.5MPa for 1 minute using a press, it is cured at 180°C / 30 minutes to make a laminate of the bonding sheet and the insulating substrate. A sample with a width of 10mm×length of 70mm is cut out from the laminate, and a peeling test is performed using a tensile testing machine with a chuck distance of 50mm and a tensile speed of 50mm / min to determine the maximum bonding strength and evaluate it. If the bonding strength is 5N / cm or more, peeling during processing such as etching-based circuit formation, through-hole formation, or desmearing can be suppressed, as well as expansion and peeling during reflow.
[0185] ◎: 6N / cm or more
[0186] ○: 5N / cm or more and less than 6N / cm
[0187] ×: less than 5N / cm
[0188] 3. Reflow resistance
[0189] The wiring board was subjected to a reflow process at a maximum temperature of 260° C. for 30 seconds three times, and the appearance of the sample after the reflow process was observed to evaluate the presence or absence of expansion and peeling.
[0190] ○: No expansion or peeling
[0191] ×: Swelling and peeling
[0192] 4. Transmission loss
[0193] The transmission loss was measured using a wiring board with a strip structure. The transmission loss at 40 GHz was measured using a network analyzer (manufactured by KEYSIGHT TECHNOLOGIES) and a probe method. By using an insulating substrate with low dielectric properties, a bonding sheet with low dielectric properties, and a low roughening metal layer (I), the transmission loss can be reduced, and an excellent high-frequency circuit substrate with a loss of less than -10.0 dB at a frequency of 40 GHz can be obtained.
[0194] [Example]
[0195] Next, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these.
[0196] 1. Production of resin composition and biaxially stretched film (insulating substrate (I))
[0197] [Example 1]
[0198] 84.5% by mass of polyphenylene sulfide resin (A) (manufactured by DIC Corporation, linear type, melting point 285°C, melt viscosity (V6) 160 Pa·s at 300°C), 15% by mass of polyphenylene ether resin (B) (manufactured by Mitsubishi Engineering Plastics Co., Ltd., glass transition temperature 210°C, hereinafter sometimes referred to as "PPE"), and 0.5% by mass of 3-glycidyloxypropyltriethoxysilane were uniformly mixed using a roller to obtain a mixture.
[0199] Furthermore, the polyphenylene sulfide resin has a carboxyl group at its molecular terminal.
[0200] Hereinafter, polyphenylene sulfide resin is described as “PPS”, and 3-glycidoxypropyltriethoxysilane is described as “silane coupling agent-1”.
[0201] Next, the obtained mixture was put into a twin-screw extruder with a vent (manufactured by The Japan Steel Works, Ltd., "TEX-30α"). Then, melt extrusion was performed under the conditions of an ejection rate of 20 kg / hr, a screw rotation speed of 300 rpm, a cylinder setting temperature of 300° C., and a resin temperature in a wire die of about 300° C., and the mixture was ejected in a strand shape, cooled with water at a temperature of 30° C., and then cut to produce a resin composition.
[0202] Next, the resin composition was dried at 140° C. for 3 hours and then put into a single-screw extruder with a full-flighted screw to be melted at 280° C. to 310° C. The molten resin composition was extruded from a T-die and then closely cooled using a chill roll set at 40° C. to prepare an unstretched sheet.
[0203] Next, the unstretched sheet was biaxially stretched to 3.0×3.0 times at 100° C. using a batch biaxial stretching machine (manufactured by Imoto Manufacturing Co., Ltd.) to obtain a film with a thickness of 50 μm. The obtained film was then fixed to a template and heat-fixed in an oven at 275° C. to produce an insulating substrate (I) of a biaxially stretched film.
[0204] Furthermore, the obtained biaxially stretched film was passed through an infrared heating furnace (equivalent to an annealing furnace) with a heating distance of 2.0 m, cooled to room temperature and rolled into a roll to obtain a biaxially stretched film (insulating substrate (I)) after annealing. The treatment conditions were a furnace temperature of 200° C., a treatment time of 60 seconds, and a tension of 10 N.
[0205] On the obtained insulating substrate (I), a nickel-copper alloy containing 35% by mass of copper is used as the material and sputtering is performed under argon gas to form a close contact layer with an average thickness of 10 nm, and then plating is performed to form a metal layer (I) (conductor layer) with a thickness of 12 μm to produce a double-sided copper-clad laminate and a single-sided copper-clad laminate.
[0206] The average particle size of particles in the produced resin composition was measured as follows.
[0207] The resin composition particles were cut at right angles to the flow direction using an ultrathin sectioning method. Next, 2000 times scanning electron microscope (SEM) photos were taken of the cut surfaces of the cut particles, and the resulting images were enlarged to A3 size. Next, 50 particles of the enlarged SEM photos were selected, the maximum diameter of each particle on the cut surface was measured, and the average particle size was calculated. As a result, the average particle size of the particles in the resin composition particles was 1.3 μm.
[0208] In addition, the resin particles containing the resin composition obtained above were subjected to SEM-energy dispersed spectrometer (EDS) analysis to analyze the components of the matrix and particles constituting the resin composition particles. The results showed that the component constituting the matrix was PPS, and the component constituting the dispersed particles was PPE resin.
[0209] Next, a circuit was formed on the obtained double-sided copper-clad laminate using a subtractive method, and a bonding sheet (manufactured by NIKKAN Industries, Ltd., "NIKAFLEX SAFY", with a thickness of 25 μm, a relative dielectric constant of 3.0, and a dielectric loss tangent of 0.005) was stacked on the circuit surface side, and then a single-sided copper-clad laminate was stacked to produce a wiring board with a strip structure designed to have a characteristic impedance of 50.
[0210] [Example 2]
[0211] The adhesive surface of a copper foil with a low dielectric adhesive (ZAC-LDC manufactured by Fujimori Industries) with an adhesive thickness of 5 μm was press-bonded to an insulating substrate (I) at 150° C. and 3 MPa for 1 minute, and then cured at 200° C. for 60 minutes to obtain a double-sided copper-clad laminate and a single-sided copper-clad laminate. Except for this, a wiring board was obtained in the same manner as in Example 1.
[0212] [Example 3]
[0213] The insulating substrate (I) and the copper foil (manufactured by Fukuda Metal, electrolytic copper foil 12 μm, Rz 1.2 μm) were directly overlapped, and the biaxially stretched film and the copper foil were thermally pressed together using a hot press at 270°C / 5 MPa to obtain a double-sided copper-clad laminate and a single-sided copper-clad laminate. A wiring board was obtained in the same manner as in Example 1, except that the above-mentioned steps were repeated.
[0214] [Example 4]
[0215] A double-sided copper-clad laminate, a single-sided copper-clad laminate and a wiring board were obtained in the same manner as in Example 1, except that the PPS resin (A) was set to 94.5% by mass and the polycarbonate resin (manufactured by Mitsubishi Engineering Plastics Chemical Co., Ltd., with a glass transition temperature of 145°C, sometimes referred to as "PC") in the thermoplastic resin (B) was set to 5% by mass.
[0216] [Example 5]
[0217] A double-sided copper-clad laminate, a single-sided copper-clad laminate and a wiring board were obtained in the same manner as in Example 1, except that the PPS resin (A) was set to 89.5% by mass and the polyethersulfone resin (manufactured by BASF, with a glass transition temperature of 225°C, sometimes referred to as "PES" hereinafter) in the thermoplastic resin (B) was set to 10% by mass.
[0218] [Example 6]
[0219] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1 except that a polyphenylene sulfone resin (manufactured by BASF, with a glass transition temperature of 220° C., hereinafter sometimes referred to as “PPSU”) was used as the thermoplastic resin (B).
[0220] [Example 7]
[0221] A double-sided copper-clad laminate, a single-sided copper-clad laminate and a wiring board were obtained in the same manner as in Example 1, except that the PPS resin (A) was set to 94.5% by mass and the polyetherimide resin (manufactured by Saudi Basic Industries (SABIC) Co., Ltd., with a glass transition temperature of 216°C, sometimes referred to as "PEI" hereinafter) in the thermoplastic resin (B) was set to 5% by mass.
[0222] [Example 8]
[0223] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1 except that a polysulfone resin (manufactured by Solvay Co., Ltd., with a glass transition temperature of 190°C, hereinafter sometimes referred to as "PSU") was used as the thermoplastic resin (B).
[0224] [Example 9]
[0225] A double-sided copper-clad laminate, a single-sided copper-clad laminate and a wiring board were obtained in the same manner as in Example 1, except that a modified fluorine-based resin having a functional group (hereinafter sometimes referred to as "modified PFA", manufactured by AGC Co., Ltd., Tg 94°C) was used as the thermoplastic resin (B) and 3-isocyanatepropyltriethoxysilane was used as the silane coupling agent.
[0226] Hereinafter, 3-isocyanatepropyltriethoxysilane is described as "silane coupling agent-2".
[0227] [Example 10]
[0228] A double-sided copper-clad laminate, a single-sided copper-clad laminate and a wiring board were obtained in the same manner as in Example 1 except that the content of the PPS resin (A) was 74.5% by mass, the PPE resin in the thermoplastic resin (B) was 10% by mass, the modified PFA resin was 15% by mass and the silane coupling agent-2 was 0.5% by mass.
[0229] [Example 11]
[0230] The composition is as follows: 82.5% by mass of PPS resin (A), 15% by mass of PPE resin in the thermoplastic resin (B), 2% by mass of Bondfast 7L (manufactured by Sumitomo Chemical Co., Ltd., ethylene / glycidyl methacrylate / methyl acrylate = 70 / 3 / 27 (mass %), hereinafter sometimes referred to as "BF7L") in the modified elastomer (C). Otherwise, a double-sided copper-clad laminate, a single-sided copper-clad laminate and a wiring board are obtained in the same manner as in Example 1.
[0231] [Example 12]
[0232] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1 except that 3-aminopropyltriethoxysilane was used as the silane coupling agent.
[0233] Hereinafter, 3-aminopropyltriethoxysilane is described as "silane coupling agent-3".
[0234] [Example 13]
[0235] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1 except that the PPS resin (A) was 85% by mass, the PPE resin in the thermoplastic resin (B) was 15% by mass, and no silane coupling agent was added.
[0236] [Comparative Example 1]
[0237] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1 except that a biaxially stretched film containing only a PPS resin was used as the insulating base material (I).
[0238] [Comparative Example 2]
[0239] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1 except that a polyimide-based adhesive ("PIAD" manufactured by Arakawa Chemical) was used as the adhesive layer.
[0240] [Comparative Example 3]
[0241] A double-sided copper-clad laminate, a single-sided copper-clad laminate, and a wiring board were obtained in the same manner as in Example 1 except that polyimide (Kapton manufactured by Dupont, thickness 50 μm) was used as the insulating base material (I).
[0242] [evaluate]
[0243] 1. Dielectric properties of insulating substrate (I)
[0244] The dielectric constant and dielectric loss tangent were measured based on the cavity resonance method specified in JIS C 2565: 1992. Specifically, a strip of 3 mm wide × 150 mm long was made from the insulating substrate (I). Next, the prepared strip was left to stand for 24 hours under an environment of 23°C and 50% Rh, and then the dielectric constant and dielectric loss tangent at a frequency of 5 GHz were measured using the cavity resonance method using the ADMS010c series (manufactured by Aet Co., Ltd.).
[0245] 2. Adhesion to the adhesive layer
[0246] The bonding layer (bonding sheet) (thickness 25 μm, 100 mm × 100 mm) and the insulating substrate (I) (100 mm × 100 mm) were overlapped, and pressed at 80°C and 0.5 MPa for 1 minute using a press machine, and then cured at 180°C / 30 minutes to produce a laminate of the bonding sheet and the film. A sample of 10 mm wide × 70 mm long was cut out from the wiring board, and a peel test was performed using a tensile testing machine with a chuck distance of 50 mm and a tensile speed of 50 mm / min to obtain the maximum bonding strength and evaluate it.
[0247] ◎: 6N / cm or more
[0248] ○: 5N / cm or more and less than 6N / cm
[0249] ×: less than 5N / cm
[0250] 3. Reflow resistance
[0251] The wiring board was subjected to a reflow process at a maximum temperature of 260° C. for 30 seconds three times, and the appearance of the sample after the reflow process was observed to evaluate the presence or absence of expansion and peeling.
[0252] ○: No expansion or peeling
[0253] ×: Swelling and peeling
[0254] 4. Transmission loss
[0255] The transmission loss was measured using a wiring board having a strip structure. The transmission loss was measured at 40 GHz using a network analyzer (manufactured by KEYSIGHT TECHNOLOGIES) by a probe method.
[0256] [Table 1]
[0257]
[0258] *PPS: Polyphenylene sulfide resin
[0259] PPE: Polyphenylene ether resin
[0260] PC: Polycarbonate resin
[0261] PES: Polyethersulfone resin
[0262] PPSU: Polyphenylsulfone resin
[0263] PEI: Polyetherimide resin
[0264] PSU: Polysulfone resin modified PFA: Modified perfluoroalkoxyalkane [Table 2]
[0265]
[0266] [Table 3]
[0267]
[0268] [Table 4]
[0269]
[0270] *PI: Polyimide
[0271] The circuit boards obtained in Examples 1 to 13 showed excellent adhesion and heat resistance.
[0272] In contrast, the circuit boards obtained in Comparative Examples 1 and 2 were inferior in adhesion and reflow resistance (heat resistance). In addition, the transmission loss of the circuit boards obtained in Examples 1 to 13 was lower than that of Comparative Example 3.
Claims
1. A circuit substrate, comprising a structure in which at least a metal layer (I), an insulating substrate (II) having a circuit formed on one or both sides, an adhesive layer on the circuit-formed surface, and an insulating substrate (II) or a metal layer (II) are sequentially stacked, wherein: The insulating substrate (I) comprises a resin composition of a polyarylene sulfide resin (A) as a main component and a thermoplastic resin (B) other than the polyarylene sulfide resin having a glass transition temperature of 140° C. or higher or a melting point of 230° C. or higher. The adhesive layer is a thermosetting resin layer containing a styrene-based elastomer.
2. The circuit substrate according to claim 1, wherein: The thermoplastic resin (B) other than the polyarylene sulfide-based resin is a dispersed phase having an average dispersed diameter of 5 μm or less.
3. The circuit substrate according to claim 1 or 2, wherein: The ratio of the blending amount of the thermoplastic resin (B) other than the polyarylene sulfide resin is in the range of 1% by mass to 49% by mass relative to 100% by mass of the total amount of the polyarylene sulfide resin (A) and the thermoplastic resin (B).
4. The circuit substrate according to claim 1 or 2, wherein: The thermoplastic resin (B) other than the polyarylene sulfide resin is a polyphenylene ether resin, a polycarbonate resin, a polyether sulfone resin, a polyphenylene sulfone resin, a polyetherimide resin, a polysulfone resin or a fluorine-containing resin.
5. The circuit substrate according to claim 1 or 2, wherein: The dielectric constant of the insulating substrate (I) is 3.3 or less.
6. The circuit substrate according to claim 1 or 2, wherein: The resin composition of the insulating base material (I) further contains a modified elastomer (C) to which a reactive group is imparted.
7. The circuit substrate according to claim 6, wherein: The modified elastomer (C) includes an olefin-based polymer having at least one functional group selected from the group consisting of an epoxy group and an acid anhydride group.
8. The circuit substrate according to claim 6, wherein: The modified elastomer (C) is blended in an amount of 1 to 15% by mass relative to 100% by mass of the total of the polyarylene sulfide resin (A), the thermoplastic resin other than polyarylene sulfide (B), and the modified elastomer (C).
9. The circuit substrate according to claim 6, wherein: The α-olefin content of the modified elastomer (C) is 50% by mass to 95% by mass based on the total mass of the modified elastomer.
10. The circuit substrate according to claim 1 or 2, characterized in that: The present invention further contains 0.01% by mass to 5% by mass of a silane coupling agent (D) containing at least one functional group selected from the group consisting of an epoxy group, an amino group and an isocyanate group.
11. A high-speed transmission cable, comprising the circuit substrate according to claim 1 or 2.
